Tell me about your day today - Fox, Mem, 1946- (Beach Lane Books, 2012)
"What could be more wonderful than sharing bedtime with beloved friends? This little boy loves to talk to his stuffed animals at the end of the day, and share with them all the things that happened to him that day--and to hear about their day, too"--